Peningkatan Kemampuan Menulis Karangan Dekripsi Dengan Menggunakan Media Gambar - Aryani Aryani (Jurnal Konseling dan Pendidikan, 2016)
Writing is a processof delivering ideas and messages, feelings and information to the readers through creative process and this activity needs knowledge and skill, so the readers can easily and clearly undertand the ideas or messages of the writer. One  of writng texts is descriptive text which describes about something.  There are some factors which make the writer can not deliver and write his or her ideas about describing something. This condition is caused by the media which is used by the teacher in the classroom is not interesting and cannot motivate the students to write descriptive text. This research is about increasing students’ability in writing descriptive text by using pictures By using pictures, the students can be motivated to write and to deliver their ideas to descrite something well.